PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR SISWA MUATAN PKN KELAS V DI SDN 015 TANDUNG, KECAMATAN TINAMBUNG, KAB. POLEWALI MANDAR - Mutmainnah; Lutfi; Bhakti Prima Findiga Hermuttaqien; Nurfaizah AP; Suarlin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problem in this study is the low learning outcomes of civics content for fifth grade students at SDN 015 Tandung, Tinambung District, Kab. Polewali Mandar, The aim of this researcher was to find out the application of the Talking Stick learning model to Civics content can improve the learning outcomes of fifth grade students at SDN 015 Tandung, Tinambung District, Kab. Polewali Mandar, This research approach is a qualitative approach. This type of research is classroom action research (PTK) which is conducted in two cycles, which include planning, implementing, observing, and reflecting. The focus of this research is the focus of the process and the focus of student learning outcomes on Civics content by applying the Talking Stick Type cooperative learning model. The subjects in this study were fifth grade students at SDN 015 Tandung, Tinambung District, Kab. Polewali Mandar for the 2022/2023 academic year, with a total of 25 students consisting of 9 boys and 16 girls, as well as a teacher. Data collection techniques used are observation, tests, and documentation. The data analysis technique used is data reduction, data presentation. The results showed that there was a significant increase in each cycle. The test results for the first cycle were in the Enough Category (C) and for the second cycle, there was an increase in Category (B). Polewali Mandar by applying the Talking Stick cooperative learning model has increased.